Pengaruh Stres Kerja terhadap Kinerja Anggota Satuan Brimob Polda XYZ dengan Dukungan Sosial - Ully Crenilia; Arumwardhani Nusandari; Rusmalia Dewi (EduInovasi: Journal of Basic Educational Studies, 2026)
This study aims to analyze the effect of work stress on the performance of Brimob members at the XYZ Regional Police with social support as a moderating variable. The working environment in police organizations, especially in the Mobile Brigade (Brimob) unit, is characterized by high-risk tasks, intensive operational mobility, and high levels of readiness. These conditions may lead to work stress that can affect the performance of members in carrying out their duties. This research employed a quantitative approach using a survey method. The sample in this study consisted of active members of the Brimob Unit of XYZ Regional Police who were selected using a purposive sampling technique. Data were collected through the distribution of questionnaires to 120 Brimob members as respondents. Data analysis was conducted using Structural Equation Modeling (SEM) to examine the relationships among variables and the role of social support as a moderating variable. The results indicate that work stress has a negative effect on the performance of Brimob members. Furthermore, social support plays an important role in moderating the relationship between work stress and employee performance. These findings provide theoretical contributions to the development of human resource management studies and practical implications for police organizations in improving member performance through effective work stress management and strengthening social support in the workplace.